Implementasi Gaya Kepemimpinan Kepala Sekolah dan Dampaknya Terhadap Kinerja Guru di MTsN 1 Probolinggo - Yaqin, Muhammad Ainul; Aditama, Hizamul Fikri; Arwani, Muhammad (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyse the leadership style of the principal and its impact on teacher performance at MTsN 1 Probolinggo. The focus of the study is on the influence of leadership on teacher performance in pedagogical, professional, and administrative aspects, particularly in the context of implementing the Merdeka Curriculum and digital transformation in education. The study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with the principal, teachers, vice principal, and supervisor, and supported by analysis of school documentation. The research location was selected purposively because MTsN 1 Probolinggo demonstrated communicative and collaborative leadership practices. The results showed that the principal implemented a democratic and participatory leadership style characterised by open communication, teacher involvement in decision-making, and providing space for learning innovation. This leadership style has a positive impact on improving teacher performance, particularly in learning planning and implementation, continuous professional development, and administrative order. In addition, the principal demonstrates adaptive abilities in responding to education policies and utilising technology. These findings confirm that collaborative and adaptive leadership plays an important role in improving teacher performance in madrasahs.